2015
DOI: 10.4252/wjsc.v7.i4.728
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties of scaffolds: Crucial parameters towards stem cells differentiation

Abstract: Tissue engineering is a multidisciplinary field that applies the principles of engineering and life-sciences for regeneration of damaged tissues. Stem cells have attracted much interest in tissue engineering as a cell source due to their ability to proliferate in an undifferentiated state for prolonged time and capability of differentiating to different cell types after induction. Scaffolds play an important role in tissue engineering as a substrate that can mimic the native extracellular matrix and the proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
128
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(129 citation statements)
references
References 110 publications
1
128
0
Order By: Relevance
“…50 The mechanical properties of biomaterials, such as electrospun PMMtissue scaffolds, should be in an appropriate range considering their intended applications. 51 The mucilage, as an organic additive material, might induce a positive effect on the tensile strength of PVA nanofibers. 52 Therefore, the mechanical properties of PMM/PVA nanofibers were investigated in order to determine the effect of PMM on pure PVA nanofiber tensile strength.…”
Section: Tensile Strengthmentioning
confidence: 99%
“…50 The mechanical properties of biomaterials, such as electrospun PMMtissue scaffolds, should be in an appropriate range considering their intended applications. 51 The mucilage, as an organic additive material, might induce a positive effect on the tensile strength of PVA nanofibers. 52 Therefore, the mechanical properties of PMM/PVA nanofibers were investigated in order to determine the effect of PMM on pure PVA nanofiber tensile strength.…”
Section: Tensile Strengthmentioning
confidence: 99%
“…The typical tissue engineering approach uses a biomaterial scaffold seeded with cells and bioactive factors. By optimizing properties of the scaffold such biocompatibility, biodegradability, porosity, mechanical properties, topography, and biochemical signaling, an extracellular environment can be created that mimics in vivo tissue and positively influences cell proliferation, differentiation, migration, and long‐term engraftment . Studies have already demonstrated the feasibility of pericyte‐based tissue engineered vascular grafts for treatment of limb ischemia , and animal models using similar cell sources have shown promising results for cardiac repair using scaffold‐based cell delivery .…”
Section: Utilizing Pericytes For Regenerative Therapymentioning
confidence: 99%
“…Mechanical properties such as tensile strength and compliance are important to the compatibility of the fiber with the weaving machine and maintenance of the desired scaffold shape. Material properties such as hydrophobicity and degradability are important considerations that will affect cellular behavior once cells have been seeded onto the construct …”
Section: Bio‐loom To Weave Scaffolds For Bone Tissue Engineeringmentioning
confidence: 99%
“…Material properties such as hydrophobicity and degradability are important considerations that will affect cellular behavior once cells have been seeded onto the construct. 9 Given the unique qualities of absorbable materials when compared with traditional threads, special consideration must be given to weaving these fibers. The term bio-loom can be defined as a textile technology-based apparatus, specialized for the weaving of absorbable fibers or yarns.…”
Section: Bio-loom To Weave Scaffolds For Bone Tissue Engineeringmentioning
confidence: 99%